Antimicrobial Resistance Patterns of Salmonella Typhi Isolated from Stool Culture - Rahman, Mohammad Atiqur (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Resistance of S. typhi to a number of antibiotics has become a serious public health problem. Drug resistant S. typhi has been reported as early as 1972 in Mexico and been observed in other countries like Bangladesh, Thailand, Vietnam, Korea, Peru and India. Methods: This cross-sectional descriptive study was carried out in Ibn Sina Microbiology laboratory, Sylhet during the period from May 2012 to September 2013 to determine the antimicrobial resistance patterns of Salmonella typhi (Salmonella enterica serovar Typhi) isolated by stool culture from clinically suspected typhoid fever patients. Stool samples were collected in clean widemouthed plastic container from 249 patients, who attended Ibn Sina Hospital, irrespective of age. The specimens were cultured on Salmonella-Shigella agar (SSA), MacConkey agar (MAC) and Xylose-Lysine-Deoxycholate (XLD) Agar media. Laboratory isolation and identification of Salmonella typhi (S.typhi) were done using standard morphological and biochemical methods. Isolates identified as S typhi were differentiated from other Salmonella species using Triple Sugar Iron (TSI) agar. Antimicrobial resistance of each isolate was determined by the Modified Kirby-Bauer disc diffusion method on Muller Hinton agar using commercially available discs following Clinical and Laboratory Standards Institute (CLSI) guidelines. The panel of antimicrobials included were amikacin (30?g), azithromycin (15?g), cefixime (5?g), ceftriaxone (30?g), ciprofloxacin (5?g), chloramphenicol (30?), co-trimoxazole (1.25/23.75?g), imipenem (10?g), levofloxacin (5?g) and tetracycline (30?g). Result: Out of 249 stool specimens investigated, only 35(14.06%) isolates of S.typhi were recovered. Among 35 positive samples 19(54.29%) were adult and 16(46.71%) were children. Antimicrobial susceptibility test showed that the resistance rates of S.typhi were 97.14% for cotrimoxazole, 95.29% for azithromycin, 91.43% for cefixime, 85.71% for tetracycline, 77.14% for ciprofloxacin and 68.57 % for ceftriaxone, respectively. Increased sensitivity was reported for imipenem (88.57%), amikacin (77.14%), chloramphenicol (65.71%) and levofloxacin (42.86%). Conclusion: Of the 35 isolates of S. typhi, none was susceptible to all of the antibiotics. We therefore face the imminent prospect of encountering untreatable typhoid fever in the near future due to multi-drug resistance pattern of isolates observed in this study. Further studies with large number of specimens are highly recommended to validate the present study and to monitor microbial trends and antimicrobial resistance patterns in other parts of Bangladesh. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22876 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 26-30